2017
DOI: 10.1002/pmic.201700214
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphoproteomics Profiling of Nonsmall Cell Lung Cancer Cells Treated with a Novel Phosphatase Activator

Abstract: Activation of protein phosphatase 2A (PP2A) is a promising anticancer therapeutic strategy, as this tumor suppressor has the ability to coordinately downregulate multiple pathways involved in the regulation of cellular growth and proliferation. In order to understand the systems-level perturbations mediated by PP2A activation, we carried out mass spectrometry-based phosphoproteomic analysis of two KRAS mutated non-small cell lung cancer (NSCLC) cell lines (A549 and H358) treated with a novel small molecule act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…S4, B and C), suggesting that these cells are already saturated for CIP2A-mediated PP2A inhibition. Finally, in the context of mTOR/AKT signaling as the mechanism of MEKi resistance resulting from PP2A inhibition, SMAP DT-061 inhibits AKT and RPS6K signaling in H358 cells (38). We confirmed that the DT-061 + MEKi combination potently inhibited the identified MEKi resistance mechanism (probed by p-AKT and MYC antibodies) in KRAS-mutant lung cancer cell lines H358 and H441 ( fig.…”
Section: Pharmacological Pp2a Reactivation Potentiates the Therapeutisupporting
confidence: 67%
“…S4, B and C), suggesting that these cells are already saturated for CIP2A-mediated PP2A inhibition. Finally, in the context of mTOR/AKT signaling as the mechanism of MEKi resistance resulting from PP2A inhibition, SMAP DT-061 inhibits AKT and RPS6K signaling in H358 cells (38). We confirmed that the DT-061 + MEKi combination potently inhibited the identified MEKi resistance mechanism (probed by p-AKT and MYC antibodies) in KRAS-mutant lung cancer cell lines H358 and H441 ( fig.…”
Section: Pharmacological Pp2a Reactivation Potentiates the Therapeutisupporting
confidence: 67%
“…These tricyclic compounds were originally derived from neuroleptic drugs that were reengineered to neutralize their CNS effects, resulting in a novel class of specific PP2A-activating compounds (51,52). Through extensive testing, SMAPs have shown remarkable efficacy and specificity in stimulating PP2A phosphatase activity toward oncogenic targets (such as phosphorylated ERK1/2) and halting the growth of lung and prostate cancer cells, both in vitro and in vivo, in a PP2A-dependent manner (53)(54)(55)(56). We transiently treated parental BON-1 cells, as well as Qgp1 cells (the only other PNET cell line available at the time of this study), overnight with increasing doses of SMAP.…”
Section: Resultsmentioning
confidence: 99%
“…PP2A activation by SMAPs simultaneously inhibits MAPK and PI3K oncogenic signaling pathways, which are downstream targets of the phosphatase, and their dephosphorylation seems to be regulated by the cellular abundance of target proteins ERK and AKT. We have shown in our recently published work that direct therapeutic activation of a phosphatase, such as PP2A, is a potentially novel strategy that aims to concurrently target several oncogenes with a single agent (16)(17)(18). Indeed, we have found that SMAPs directly bind to and activate PP2A in KRAS-mutant LUAD, therefore inhibiting tumor growth and inducing apoptosis in mouse xenografts, PDX models, and the transgenic KRAS LA2 murine model (17).…”
Section: Discussionmentioning
confidence: 99%
“…Our lab has successfully developed a published series of first-in-class small molecule activators of PP2A (SMAPs), which directly bind to PP2A and induce apoptosis and tumor growth inhibition in both transgenic and xenograft KRAS-driven mice models (16)(17)(18). SMAPs have been generated by repurposing and reengineering FDA-approved tricyclic neuroleptics through replacing the basic amine with a neutral polar functional group (19).…”
Section: Introductionmentioning
confidence: 99%